ORGANISASI PEMBELAJARAN, KOMPETENSI DAN KINERJA KARYAWAN BANK BRI DI JAKARTA - Rahardjo, Thea H. (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2016)
His study aimed to determine empirically the retail mix in small business retail, that includes Physical Facilities Merchandising, pricing, promotion, services and Organization/Personil, as a predictor of the performance of small retail businesses and competitive advantage. The method used in sampling was purposive sampling, a total of280 respondents drawn at small retail businesses in Tangerang. The data analysis technique used is Structural Equation Modeling (SEM), using by LISREL versi 8.8 are need to test the hypothesis. The results showed, retail mix small business strategy that includes Physical Facilities Merchandising, services and Organization/Personil can be used to predict the performance of retail, which means that the research hypothesis tested. While pricing, promotion can not be used to predict the performance of retail. Furthermore, the retail business performance can be used to predict the competitive advantage. Through these results can be material for the attention of small retail businesses to keep improving the combination of retail mix, either already affect or not affect the performance of the business, because through good performance can affect the competitive advantage for retailers in running the business.